A conflict analysis on the maritime border dispute between Lebanon and Israel - Ismail, Abbas (2021)
The sea is an essential component of national sovereignty and security, trade, energy production, mineral extraction, travel and is the source of today's blue economy. However, coastal countries can only fully benefit of it, if their maritime boundaries are solved with their neighbours. Currently, half of the world's maritime boundary disputes remain unresolved. The three most common methods of resolving, managing or transforming boundary disputes are negotiation, mediation and arbitration. Nevertheless, these procedures are difficult when two countries are in a state of war and do not have diplomatic relations. This is the case of Lebanon and Israel. Lebanon agreed to sit down at the negotiating table with Israel in October 2020 to finally demarcate the maritime border in the eastern Mediterranean, which was achieved through ten years of shuttle diplomacy by the USA. The indirect negotiations took place shortly after Israel had normalised its relations with the United Arab Emirates and Bahrain. This study analysed a decade of maritime border conflict between Lebanon and Israel from December 2010 to May 2021 and examined whether these rare negotiations could lead to the establishment of diplomatic relations between the two countries. The case study was analysed using three different conflict analysis tools (conflict assessment, relational conflict mapping, stakeholder analysis) and discussed by using the theoretical concept of diplomacy and conflict resolution. The results show that Lebanon would like to maintain the status quo of the current situation, but a maritime border agreement would allow for lucrative gas deals and bring the country out of its current economic crisis. However, this would not necessarily guarantee peace between the two countries and is unlikely to have a positive impact on the prospects for diplomatic normalisation between the two countries.